Selected parameters of soil health in Cumilla district at the Golden Jubilee of Bangladesh and strategies for their sustainable improvement towards rice production - Rashid Khan, Md Harunor; Akter, Suma (Dhaka University Journal of Biological Sciences, 2022)
Soil fertility and rice production were the most frequently mentioned issues identified not only in all the countries of Asia but also in the rest of the world. Hence, it is essential to pay attention for sustainable rice production, climate-smart agriculture and soil health. Accordingly, assessments of selected soil health indicators, such as, pH, organic matter and cation exchange capacity (CEC) in all 17 Upazilas of Cumilla district of Bangladesh were completed under the financial support of the Climate Change Trust Fund (CCTF). A few strategies were used for the improvement of soil health in response to smart rice production at the field site using locally available organic-fertilizers, viz. Vermicompost (V), Rice husk ash (RHA) and Burned poultry litters (BPL) at the rates of 0, 4 and 8 t ha-1 under the soil temperature elevation of 2 to 3°C (i.e. 25 to 28°C) and moisture levels of 60 and 90%. The above mentioned parameters of soil health at the Golden Jubilee of Bangladesh were found to be improved slightly compared to those of the 1970s and 2000s. These trends of improvement were found to be enhanced by the stated treatments. The yields of different rice varieties were increased from 4.4 - 5.5 to 8.4 – 9.1 t ha-1 by the treatments and the order of their effectiveness for grain yields and protein contents were V > BPL > RHA. Organic matter contents, pH and CEC of the studied soils were increased by these treatments and decreased CH4 emissions from the studied rice field. However, these approaches of sustainability cannot be provided by the poor farmers and therefore, the government should come forward to help these farmers in order to build a ‘Developed Bangladesh’ – the dream of Bangabandhu Sheikh Mujibur Rahman, the Father of the Nation and the Honorable Prime Minister Sheikh Hasina, the Mother of Humanity and the Champion of the Earth. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 511-531, 2022 (June)